2021
DOI: 10.1007/s00477-021-01991-5
|View full text |Cite
|
Sign up to set email alerts
|

A multi-state Markov chain model to assess drought risks in rainfed agriculture: a case study in the Nineveh Plains of Northern Iraq

Abstract: The occurrence of prolonged dry spells and the shortage of precipitation are two different hazardous factors affecting rainfed agriculture. This study investigates a multi-state Markov chain model with the states of dry spell length coupled with a probability distribution of positive rainfall depths. The Nineveh Plains of Northern Iraq is chosen as the study site, where the rainfed farmers are inevitably exposed to drought risks, for demonstration of applicability to real-time drought risk assessment. The mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…It can be seen from the algorithm flow that the algorithm includes two layers of loops. The inner loop represents the random search of the state at the same temperature, while the outer loop is the change when the temperature drops and the algorithm stops conditions [ 38 ]. According to this characteristic, SA can help the neural network jump out of local optimum.…”
Section: Construction Of the Obesity Monitoring Model Based On Sa Algorithmmentioning
confidence: 99%
“…It can be seen from the algorithm flow that the algorithm includes two layers of loops. The inner loop represents the random search of the state at the same temperature, while the outer loop is the change when the temperature drops and the algorithm stops conditions [ 38 ]. According to this characteristic, SA can help the neural network jump out of local optimum.…”
Section: Construction Of the Obesity Monitoring Model Based On Sa Algorithmmentioning
confidence: 99%
“…Several researches have been done in Iran on drought monitoring and forecasting using drought indicators and Markov chain model; Among other things, in a study in the Salt Lake basin, which was conducted using several indices, including the decimal index, the normal percentage index, and the standard bar 1 index, it was shown that the standard precipitation index is the most suitable index for evaluating the severity of drought ( Fadhil et al 2021) and (Guo et al…”
Section: )mentioning
confidence: 99%
“…For the verification of the empirical distribution with the theoretical distribution, nonparametric consistency tests are commonly used [52][53][54]. The choice of test depends on the type of distribution being verified, the random variable and the sample size.…”
Section: Statistical Analysis Of Datamentioning
confidence: 99%